Edge Detection in an Image by Using the Elimination Rule - Hameed, Maha (Iraqi Journal of Science, 2024)
Edges are significant local changes of intensity in an image. In this paper, anelimination rule which based on triangular inequality elimination (TIE) has beenadopted to perform the edge detection procedures. A new method has been includedthe combining between an elimination rule which based on triangular inequalityelimination (TIE) and the differentiation operator by using the filters mask in onedimension. The introduced algorithm has been produced a good image quality bycomparison with that which may be obtained by using the differentiation operator ofsharpening an image. The proposed algorithm has been proved it is good for findingthe edge in an image data.